Realizacja procesów restrukturyzacji i rozwoju przedsiębiorstwa z wykorzystaniem strategicznej karty wyników - Piechota, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article concerns the possibility to implement the Balanced Scorecard in the processes of enterprise restructuring. Balanced Scorecard lets identify precisely those areas of an enterprise which require restructuring. Balanced Scorecard is of special significance in the conditions of crisis. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 324-332